Siglind Bruhn i pieśniowe symfonie o przemijaniu - Trzęsiok, Marcin (Res Facta Nova, 2021)
This article discusses Siglin Bruhn’s book “Dunkel ist das Leben”. Liedsinfonien zur Vergänglichkeit von Mahler bis Penderecki (2020). It summarises the main theses of the book, i.e., the content of the selected symphonies about transience (Mahler, Zemlinsky, Shostakovich, Penderecki) and the methodological decision to base analyses primarily on the vocal line shown in a particular typographic arrangement that reflects the formal structure of poetry. The review focuses specifically on the analyses of two late vocal symphonies by Krzysztof Penderecki (Sixths and Eighth), which Siglind Bruhn’s book subjects for the first time to such complex scholarly interpretation.